(untitled) (NTU Journal of Agriculture and Veterinary Science, 2022)
The current study was conducted in the apiary of the College of Agriculture & Forestry/ University of Mosul during the year results that showed the highest mean amount of bee venom for the interaction reading0.1207 mg/colony in the treatment of milking bee population of 10 frames (TMV2) during the period from 7-12/8/2021 compared with the lowest mean interaction of 0.0067 mg/colony which was recorded during the period from 16-21/10/2021 for the same treatment. However, the highest mean interaction for the treatment of milking bee venom population was 5 frames (TMV1) during the period from 21-26/8/2021 which was 0.0810 mg /colony compared with the lowest mean of 0.0023 mg/colony during the period from 16-21/10/2021 for the same treatment. As for the treatments general mean, the highest mean was recorded in the TMV2 treatment which amounted to 0.0644 mg/colony compared with the lowest general mean of zero mg/colony in the TCM2 treatment. As for the milking treatment of TMV1,the highest mean was recorded 0.0305 mg/colony in the TMV1 treatment compared with the lowest average of zero mg/colony in the TCM1 treatment. As for the process effect of the bee venom milking on daily mortality of workers, the daily mortality was increased by 3.47 worker/day in TMV2 which recorded a mean of 6.99 worker/day compared with the TCM2 treatment which, in turn, recorded a mean of 3.52worker/day. As for the treatments with a bee population of five frames, the daily mortality of workers was increased by 3.2 worker/day in the treatment of TMV1 treatment which recorded the lowest mean of 5.78worker/day compared with the TCM1 treatment which recorded a mean of2.58worker/day. Regarding the general mean of the fat content, the statistical analysis did not show any significant differences between the two treatments TMV2 and TCM2 whose means reached 21.10 and 20.93 % respectively. As for the treatments with fat content of five frames, the highest mean was recorded in a treatment TMV1 amounting to17.50 % compared with the lowest mean which was 15.38 % recorded in TCM1 treatment. As for the Nitrogen content in treatments with a bee population of 10 frames, the highest mean was recorded in the TMV2 treatment which amounted to9.37 % compared with the lowest mean in the TCM2 treatment which amounted to 8.11%.The statistical analysis did not show any significant differences for the effect of milking bee venom in the Nitrogen content for the treatments with a bee population of five frames, and the highest mean was recorded in the TMV1 treatment which amounted to7.77 % compared with the lowest mean of 7.75% which was recorded in the TCM1 treatment. As for the acidity (pH) in workers abdomen, the statistical analysis did not show any significant differences for the effect of milking bee venom in the acidity (pH) in workers abdomen for the treatments with a bee population of ten frames.